LEGAL ANALYSIS OF THE STATUS OF INHERITANCE RIGHTS OF CHILDREN BORN FROM A SURROGATE MOTHER AGREEMENT REVIEWED ACCORDING TO POSITIVE LAW - Febrina Andarina Zaharnika (Proceeding International Conference on Social Sciences, 2026)
Basically, regulations related to surrogacy do not have specific provisions governing surrogate mothers. Therefore, regarding the provisions of Article 127 paragraph (1) of the Health Law, there is an agreement with the provisions of Law Number 39 of 1999 in Article 10 paragraph (1), which states that in order to continue the lineage, a legal marriage is required. Therefore, from the perspective of Islamic law and civil law, a child born outside of a legal marriage only has a civil relationship with the mother and the mother's family. The child is not entitled to inheritance rights or support from the biological father. Therefore, in Islamic law, there is no "child of adultery"; there is only "a child born outside of a legal marriage" whose status is the same as a child born from a relationship between a man and a woman without the bonds of a legal marriage. Therefore, the status of an illegitimate child cannot be said to be a legitimate child. The method used in this writing is a qualitative research method with a normative juridical approach. The results of this study aim to relate to the policy of the Constitutional Court Decision No. 46/PUU-VIII/2010 concerning the review of Article 43 paragraph (1) of the Marriage Law regulates the recognition of civil relations between illegitimate children and their fathers, as follows: Children born out of wedlock have a civil relationship with their mother and their mother's family as well as with the man as their father who can be proven based on science and technology and/or other evidence according to the law to have a blood relationship, including a civil relationship with their father's family. Therefore, in the provisions of Articles 862 to 873 of the Civil Code regarding the conformity of the Civil Code regulations, inheritance only applies to illegitimate children who are recognized by their father and/or mother. Without recognition from the father and/or mother, illegitimate children do not have the right to inherit.